"The biggest barrier is to inclusion itself": the experience of citizenship for adults with mental health problems. (4th May 2021) - Cogan, Nicola Ann; MacIntyre, Gillian; Stewart, Ailsa; Tofts, Abigail; Quinn, Neil; Johnston, Gordon; Hamill, Linda; Robinson, John; Igoe, Michael; Easton, Duncan; McFadden, Anne Marie; Rowe, Michael
Abstract: Background: Citizenship has been promoted within mental health for several decades however, its application in the field of mental health policy and practice is relatively novel. The voices of people who experience mental health problems (MHPs) are often absent in ongoing discourses about citizenship. Aims: To explore how adults with experience of MHPs and other life disruptions identify potential barriers to citizenship. Method: A community based participatory research approach was adopted with peer researchers. Six focus groups (N = 40) using semi-structured interviews were conducted, consisting of participants who had experience of MHPs and other life disruption(s) within the last 5 years. The focus groups were audio recorded, transcribed verbatim and analysed in NVIVO using a thematic approach. Results: Three major themes associated with participants lived experiences of barriers to citizenship were identified: 'stigmatisation (internal & external) creates further divide'; 'being socially excluded leads to isolation'; and 'a sense of difference (as perceived by the self and others)'. Conclusions: Those who have experienced major life disruption(s) face multi-level barriers to citizenship. An awareness of such barriers has important implications for mental health research, policy and practice. Citizenship-oriented implementation strategies that aim to address multi-level barriers merit further investigation.